2022
DOI: 10.3390/molecules27217604
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechins Attenuate Neurodegenerative Diseases and Cognitive Deficits

Abstract: Neurodegenerative diseases exert an overwhelming socioeconomic burden all around the globe. They are mainly characterized by modified protein accumulation that might trigger various biological responses, including oxidative stress, inflammation, regulation of signaling pathways, and excitotoxicity. These disorders have been widely studied during the last decade in the hopes of developing symptom-oriented therapeutics. However, no definitive cure has yet been discovered. Tea is one of the world’s most popular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 190 publications
0
13
0
1
Order By: Relevance
“…It activates Nrf2, and it is known for its antioxidant and health-promoting properties [ 191 ]. Research suggests that ECCG may help protect neurons from oxidative damage and improve cognitive function [ 192 ]. Quercetin, found in fruits and vegetables, is an Nrf2 pathway activator that reduces inflammation and improves antioxidant defense mechanisms.…”
Section: Signaling Pathway Modulators For Cellular Antioxidant Synthesismentioning
confidence: 99%
“…It activates Nrf2, and it is known for its antioxidant and health-promoting properties [ 191 ]. Research suggests that ECCG may help protect neurons from oxidative damage and improve cognitive function [ 192 ]. Quercetin, found in fruits and vegetables, is an Nrf2 pathway activator that reduces inflammation and improves antioxidant defense mechanisms.…”
Section: Signaling Pathway Modulators For Cellular Antioxidant Synthesismentioning
confidence: 99%
“…For years, tea has been increasingly popular due to its unique flavor and diversified health efficacy . Green tea is one of the six major teas made from the leaves of the plant Camellia sinensis, conferring polyphenols with potential therapeutic effects on ND . Flavonoids, a subclass of polyphenols with multiple beneficial biological effects, are classified into flavonols, flavones, isoflavones, flavavones, anthocyanins, and flavanols .…”
Section: Introductionmentioning
confidence: 99%
“…6 Green tea is one of the six major teas made from the leaves of the plant Camellia sinensis, conferring polyphenols with potential therapeutic effects on ND. 7 Flavonoids, a subclass of polyphenols with multiple beneficial biological effects, 8 are classified into flavonols, flavones, isoflavones, flavavones, anthocyanins, and flavanols. 9 Myricetin, quercetin, and kaempferol are naturally occurring flavonols widely present in tea, fruits, vegetables, and other natural foods and can inhibit protein aggregates related to AD.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several studies have revealed that a large number of natural compounds derived from plants, animals and 2 of 20 microorganisms have the potential to inhibit oligomerization [11,12,[18][19][20]. For example, several computational and experimental observations have shown that polyphenolic plant compounds which occur naturally in fruit, vegetables, chocolate, and tea are capable of inhibiting IDP aggregation [12,13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, a computational pipeline in the framework of the ensemble docking strategy has been proposed to identify catechins' binding sites on the full-length human amyloid-β (Aβ 42 ) monomer which is involved in Alzheimer's disease [2,5,11,12,27,39,41,43]. Catechins (or flavan-3-ols) are dietary polyphenolic compounds commonly found in green tea and their inhibitory effects on Aβ aggregation have been the subject of numerous experimental and computational investigations [21,28,36,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. There is experimental evidence indicating that the catechins are able to disturb Aβ aggregation and change the aggregation process toward the formation of non-toxic oligomers [28,37,77,78,80,81,85,86].…”
Section: Introductionmentioning
confidence: 99%